Technologies for Enhancing Efficiency in Transportation Management - Seahapong, Jintana; Boonraksa, Nantawan (Business Administration and Management Journal Review, 2025)
This article aims to present the application of technology, including Barcode, RFID, GPS, ERP, EDI, and TMS, in enhancing transportation management efficiency. Transportation is a critical process that links production sources with consumers by facilitating the movement of goods from their origin to locations where they are needed or consumed, thereby creating value in terms of time and place. Technology plays a vital role in ensuring accuracy and timeliness in receiving and delivering goods, enabling real-time tracking and monitoring of shipment status, reducing operational costs, and maintaining service quality.